The protective effects of propolis and flunixin meglumine on feed intake, antioxidant status and histological parameters in liver and kidney tissues against excess copper in rats - Tatli Seven, Pinar; Gul Baykalir, Burcu; Parlak Ak, Tuba; Seven, Ismail; Basak, Nese; Yaman, Mine (Ankara Univ Press, 2018)
This experiment was conducted to determine the protective effects of flunixin meglumine and propolis on feed intake, antioxidant status and histological parameters in kidney and liver tissues in rats exposed to excessive copper. In this study individually housed thirty-six male Sprague-Dawley rats were used. Animals were randomly divided into six groups; control, copper sulphate (500 mg/kg BW/day, gavage), flunixin meglumine (2.2 mg/kg BW/day, ip), propolis (100 mg/kg BW/day, gavage), copper sulphate+flunixin meglumine (500 mg/kg BW/day of copper sulphate by gavage and 2.2 mg/kg BW/day of flunixin meglumine, ip) and copper sulphate+propolis (500 mg/kg BW/day of copper sulphate and 100 mg/kg BW/day of propolis by gavage). The study demonstrated that body weight change in the copper sulphate+propolis group significantly ameliorated in comparison with copper group (P < 0.01). Propolis and flunixin meglumine administration significantly decreased MDA levels in the kidney and liver tissues, and serum TNF-alpha levels (P < 0.001). Propolis supplementation to rats who were also treated with copper significantly increased the superoxide dismutase, catalase and reduced glutathione activities (P < 0.001). Flunixin meglumine and propolis treatments decreased the copper-induced degenerative and necrotic changes with the apoptotic cells in the liver and kidney tissues. In conclusion, propolis appeared to ameliorate the adverse effects on feed intake, liver and kidney tissues seeing in the copper treatment and, apparently caused by the copper toxicity, by scavenging the free radicals and increasing activity of antioxidants.
Ratlarda bakır fazlalığına karşı yem tüketimi, antioksidan durum ve karaciğer ile böbrek dokularının histolojik parametreleri üzerine propolis ve fluniksin meglümin'in koruyucu etkileri
Keywords: Antioxidant status; copper; flunixin meglumine; histological changes; propolis